Pelatihan Kepemimpinan dan Digital Marketing sebagai Upaya Peningkatan Kemandirian Ekonomi Masyarakat di Era Teknologi di Yayasan Tajaul Karomatu Desa Situ Gadung Kabupaten Tangerang - Indria Rahma; Rafael Hafizdin Bachri; Yoga Ananda Gusti Pramudya; Laila Irawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid advancement of technology has created both opportunities and challenges for communities in improving their economic independence. Leadership skills and digital marketing competencies have become essential factors in empowering individuals to adapt to the digital era and enhance their economic potential. Therefore, a Community Service Program (PKM) was conducted at Tajaul Karomatu Educational Foundation, Situ Gadung Village, Tangerang Regency. The purpose of this program was to enhance participants’ understanding and skills in leadership and digital marketing to support economic self-reliance. The program was implemented on August 31, 2025, by three lecturers from Pamulang University. A total of 20 participants consisting of teachers and staff members attended the training. The implementation method included material presentations, practical sessions, discussions, and question-and-answer activities. The PKM activities were carried out through three stages: preparation, implementation, and reporting. The results of the program indicated an increase in participants’ knowledge and awareness regarding effective leadership and the utilization of digital marketing strategies. Participants demonstrated greater understanding of digital platforms and their potential use in supporting entrepreneurial and economic activities. Overall, the training contributed positively to strengthening participants’ competencies and encouraging greater economic independence in the technology-driven era.